Fabrication of fully degradable branched poly (lactic acid) nanofiber membranes for high‐efficiency filter paper materials. Issue 47 (30th September 2022) - Sun, Ning; Shao, Weili; Zheng, Jin; Zhang, Yuting; Li, Junli; Liu, Simeng; Wang, Kai; Niu, Jingyi; Li, Bo; Gao, Yanfei; Liu, Fan; Jiang, Huadong; et al.
Abstract: Air pollution caused by particulate matter (PM) poses an imminent threat to the global environment and public health. However, balancing the removal efficiency and pressure drop of most filter materials is difficult. Moreover, filter materials are non‐degradable and non‐recyclable, causing serious harm to the environment. Herein, a strategy to create fully degradable branched poly (lactic acid) (PLA) nanofibers based on electrospinning by adjusting the spinning solution properties was reported and branched PLA nanofibers were applied as nanofiber filter paper for air filtration materials. When the PLA and tetrabutylammonium chloride concentrations were 8 and 5 wt%, respectively, PLA nanofibers with branched structures were obtained. The obtained nanofibers possessed a small pore size (0.70 μm), high porosity (92.3%), appropriate mechanical properties, resulting in high PM0.3 removal efficiency (99.95%), low air resistance (79.67 Pa), and promising long‐term PM2.5 purification. Notably, branched T‐PLA‐5 nanofibers exhibited excellent filtration performance when applied to cellulose wood pulp paper. The filtration efficiency of the nanofiber filter paper remained stable above 85% for PM0.3 (32 L min −1 ) after 5000 backflushings. Thus, the preparation of such nanomaterials may provide new insights into the design and development of high‐performance degradable filtration materials for various applications. Abstract :